The Effect of Earnings Management and Capital Structure on Financial Performance with Corporate Social Responsibility Intervention Variables - Dwi Sri Rezeki; Wisnu Panggah Setiyono (Indonesian Journal of Law and Economics Review, 2022)
This study aims to determine the effect of earnings management and capital structure on financial performance with corporate social responsibility as an intervention variable in mining companies listed on the Indonesia Stock Exchange in 2014-2019.The method used in this research is a quantitative approach. The data used in this study are the financial statements of mining companies listed on the Indonesia Stock Exchange. The analysis technique used in this research is path analysis with the help of the SmartPLS 3.0 program.The results showed that earnings management has an effect on financial performance. Earnings management has no effect on corporate social responsibility. Capital structure influences financial performance. Capital structure influences corporate social responsibility. Corporate social responsibility has no effect on financial performance. Earnings management has no effect on financial performance with corporate social responsibility as an intervening variable. Capital structure has no effect on financial performance with corporate social responsibility as an intervening variable.